Učni prostor Volksschule Graz Mariagrün z vidika pedagogike - Horvat, Barbara (Šport (Ljubljana), 2022)
In this paper we deal with the primary school, Volkschule Graz Mariagrün, which is considered a case study of one of the Austrian public schools. It is a new building for pupils ages 6 to 10 years old, which operates according to the reform-pedagogical concept of the Jena-plan. The latter is analysed in particular in terms of the organization of lessons and teaching methods, and how the ideas of this pedagogical concept are realised through the internal learning space of the Graz Mariagrün School, following the architectural concept of the cluster. We find that the classrooms are mainly suitable for frontal teaching, while the learning island is also suitable for other forms and modes of teaching. The island is thus identified as a space where, unlike classrooms, it is possible to implement learning more consistently tailored to the pupil's needs, more responsive to the pupil's pace, and more diverse in the choice of learning location and the content and materials to be used, which is essential for the realisation of the principle of inclusion. We identify the constructive spatial conditions for learning as those in which the space is not typified in either form or content, since as such it essentially allows the teacher to construct it himself through the learning content in relation to the perspective of the individual learner. We conclude that this is probably an open space that is transparent, easily accessible for learners and teacher and regularly adaptable to their needs and desires, allowing communication in different directions in different ways.
Keywords: arhitektura; Jena-plan; pedagogika; pouk; šole; študije; zgradbe